Long-Term Results of Ahmed Glaucoma Valve in Association With Intravitreal Bevacizumab in Neovascular Glaucoma. Issue 5 (June 2015) - Sahyoun, Marwan; Azar, Georges; Khoueir, Ziad; Antoun, Joelle; Kourie, Hampig; Nehme, Joseph; Jalkh, Alexandre
Abstract : Purpose: Evaluate the long-term results of the Ahmed glaucoma valve (AGV) surgery in association with bevacizumab (Avastin) in neovascular glaucoma (NVG) patients. Design and Methods: This retrospective institutional study reviewed 39 eyes of 34 patients with NVG who underwent AGV implantation. The intravitreal bevacizumab (IVB) group included 19 eyes that received an injection of IVB 7 days preoperatively, whereas the no-IVB group included 20 eyes that did not receive any antivascular endothelial growth factor therapy. Findings such as intraocular pressure (IOP), number of antiglaucoma medications, best-corrected visual acuity (BCVA), and surgical outcomes were reviewed over a period of 5 years. Results: There were no significant differences in the preoperative characteristics between the 2 groups. At last follow-up visit, IOP was 16.37±5.72 mm Hg in the IVB group and 20.05±9.75 mm Hg in the no-IVB group ( P =0.16). The number of postoperative antiglaucoma medications was significantly lower in the IVB group ( P =0.02). Last visit's mean BCVA was 2.34±1.00 logMAR in the IVB group and 2.66±1.04 logMAR in the control group ( P =0.33). Hyphema was significantly less observed in the IVB group ( P =0.02). The probability of success was 63.2% in the IVB group and 70.0% in the control group ( P =0.37). Conclusions: Preoperative IVB before AGV was not associated with a better surgical success, IOP control, or BCVA. Its administration significantly decreased postoperative hyphema and number of last visit's antiglaucoma medications.